Pandangan Mahasiswa Terhadap Pembelajaran Berbasis Proyek pada Mata Kuliah Membaca dan Menulis Lanjut - Eka Rahmawati (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2023)
In the XXI century students as agents of change are required to have several skills, one of which is learning and innovation skills including critical thinking and problem solving (critical thinking and problem solving), communication (communication), collaboration (collaboration), and creative thinking (creativity), which is called 4C skills. To answer these challenges, it is necessary to apply learning methods that can involve students in real life, one of which is project-based learning methods. Mandarin Language Education Department, Faculty of Language and Arts, State University of Jakarta (PSPBM FBS UNJ) has carried out project-based learning since the even semester of the 2019/2020 academic year. However, there has never been any evaluative research on this learning method This study aimed to determine students’ view on project-based learning in reading and writing courses to improve 4C skills. The scope of view in this study was investigated using the theory of Priyanto, Brown, Widodo, and Wardani regarding 4C skills and the theory of Daryanto, Jupriadi and Silitonga regarding project-based learning. The study used descriptive qualitative with a survey method. The respondents of this study were 41 students who had taken reading and writing courses I-II in academic year of 2020/2021 and 2021/2022 at PSPBM FBS UNJ. The results showed that students agreed that project-based learning in Advanced Reading and Writing courses I-II could be used to improve 4C skills.